Computational assessment of Nano-particulate (Al2O3/Water) utilization for enhancement of heat transfer with varying straight section lengths in a serpentine tube heat exchanger. (1st December 2020) - Awais, M.; Saad, M.; Ayaz, Hamza; Ehsan, M.M.; Bhuiyan, Arafat A.
Highlights: Influence of Al2 O3 /water Nano-fluid on heat transfer was studied. Various flow rates & cross sectional serpentine tubes were investigated. Low-High serpentine tube provided comparatively higher heat transfer. Highly concentrated nanoparticles provide higher heat transfer coefficient. Abstract: A CFD-approach was employed for extensive exploration of thermo-hydraulic performance of serpentine tube heat exchanger (STHX). The prominent focus was given to the momentous factors which impart noteworthy role in acquiring desired heat transfer and pressure drop performance of heat exchanger. The impact of various volumetric flow rates (1 L/min to 5 L/min) and various cross-section lengths of serpentine tubes such as uniform, high-to-low-to-high (H-L-H), low-to-high-to-low (L-H-L) and low-to –high (L-H) were considered to acknowledge their effect on heat transfer and pressure drop characteristics. Furthermore, the influence of Al2 O3 /water-based Nano-fluid on thermo-hydraulic performance was broadly studied with the inclusion of different nanoparticles concentration (1%, 3% and 5%) under different volumetric flow rates (1–5 L/min). It was noticed that L-H serpentine tube provided comparatively higher heat transfer performance than the other cases. The promising results were obtained when higher volumetric flow rate of working medium was utilized e.g. for L-H serpentine tube at 5 L/min volumetric flow rate of water heat transfer coefficient and pressure drop was 43.8% and 95% higher than 1 L/min volumetric flow rate. Moreover, highly concentrated nanoparticles provided higher heat transfer coefficient at the expense of negligible pressure drop, e.g. for uniform serpentine tube at 5 L/min volumetric flow rates heat transfer coefficient is 50% higher for fluid with 5% volumetric concentration of nanoparticles than base fluid. To conclude, the performed computational assessment provides substantial optimal results to avail desire thermo-hydraulic performance of STHX.